Pengaruh Periklanan, Promosi Penjualan Dan Word Of Mouth Terhadap Keputusan Pembelian (Studi Pada Usaha Aneka Kerupuk Di Desa Siwalan) - Muhammad Jamaluddin; Fathor A.S (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The purpose of the study was to determine the effect of Advertising, Sales Promotion and of Mouth on purchasing decisions either partially or simultaneously. This research uses quantitative description method. The sampling technique used purposive sampling method, in order to obtain a sample of 96 people and hypothesis testing using multiple linear regression analysis. The conclusion from this research is that advertising partially has a significant effect on purchasing decisions, sales promotions have a significant effect on purchasing decisions, word of mouth partially has a significant effect on purchasing decisions and advertising, purchase promotion and word of mouth simultaneously have a significant effect on purchasing decisions.